Desmoplastic Astrocytoma of Infancy: a Case Report With Histopathologic and Immunohistochemistry Profile - Rodríguez-Morales, Edda L.; Correa-Rivas, María S.; Colón-Castillo, Lillian E. (Puerto Rico Health Sciences Journal, 2013)
see manuscript